2020
DOI: 10.1590/1413-7054202044015620
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of apple trees to irrigation water depth in a semiarid region of Brazil

Abstract: The present study evaluated the physiological and biochemical parameters of apple trees under different irrigation water depths in a semiarid region of Brazil. The experiment had a split-plot randomized block design. Irrigation levels (60, 80, 100, and 120% of the reference evapotranspiration - ET0) and two apple cultivars (Julieta and Princesa) were analysed in the experimental plots and the phenological stages (vegetative, flowering and fruiting) were analysed in the experimental subplots. The physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The reduction in water application implies a lower water availability for plant uptake, which normally promotes a reduction in stomatal opening, reducing the leaf transpiration process with a consequent decrease in CO 2 input and its availability to the mesophyll cells, affecting the photochemical and biochemical phases, which implies the reduction of photosynthetic activity (Figure 2). Thus, it is observed that both water excess and water restriction hamper the CO 2 concentration in the substomatal chamber and consequently between the cells that form leaf tissues, directly interfering in the photosynthetic process (Andrade et al, 2017;Taiz & Zeiger, 2017;Oliveira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in water application implies a lower water availability for plant uptake, which normally promotes a reduction in stomatal opening, reducing the leaf transpiration process with a consequent decrease in CO 2 input and its availability to the mesophyll cells, affecting the photochemical and biochemical phases, which implies the reduction of photosynthetic activity (Figure 2). Thus, it is observed that both water excess and water restriction hamper the CO 2 concentration in the substomatal chamber and consequently between the cells that form leaf tissues, directly interfering in the photosynthetic process (Andrade et al, 2017;Taiz & Zeiger, 2017;Oliveira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…According to the variables that contribute to the determination of gas exchange, the lower the water availability, the lower the flow from the root to the shoot, the lower the volume of water that reaches the leaves, and consequently the lower the stomatal opening, transpiration and photosynthesis, leading to the decrease of WUEi, so plants suffer from water stress (Oliveira et al, 2020;Vélez-Sánchez et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing sugars under irrigation level of 70% ETc is likely due to the reduction of translocation of these photoassimilates to the drains. Accumulation of free sugars in the leaves may be due to the disturbances caused by stressful conditions such as the reduction of water content in leaf tissues, reducing the translocation of sugars to other organs 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Fahim et al 16 reported the synthesis of soluble sugars in the cytosol is probably prioritized to maintain the plant's metabolic activity, even when water deficit reduces the rate of CO 2 assimilation. Meanwhile, Oliveira et al 15 reported that the accumulation of free sugars in the leaves with decreasing water content in the soil maintains cell turgor contributing to plant functioning. However, in order to confirm osmotic adjustment, assessing other physiological parameters that were not investigated in these studies is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation